2022
DOI: 10.1101/2022.10.14.512318
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Glycolytic reprogramming underlies immune cell activation by polyethylene wear particles

Abstract: Primary total joint arthroplasties (TJAs) are widely and successfully applied reconstructive procedures to treat end-stage arthritis. Nearly 50% of TJAs are now performed in young patients, posing a new challenge: performing TJAs which last a lifetime. The urgency is justified because subsequent TJAs are costlier and fraught with higher complication rates, not to mention the toll taken on patients and their families. Polyethylene particles, generated by wear at joint articulations, drive aseptic loosening by i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 54 publications
1
19
0
Order By: Relevance
“…However, many prior in-vitro models on PLA biocompatibility focused on acidity, based on prior correlation between reduced pH and the adverse immune responses elicited by PLA 5,19 . Instead, this study builds on observed alterations in bioenergetics as well as metabolic reprogramming as drivers of adverse immune responses to polyethylene wear particles 41,42 after total joint replacements and PLA biomaterials 6 . By subcutaneously implanting sterile amorphous PLA, we validated this bioenergetic model by demonstrating metabolic reprogramming, in-vivo.…”
Section: Discussionmentioning
confidence: 99%
“…However, many prior in-vitro models on PLA biocompatibility focused on acidity, based on prior correlation between reduced pH and the adverse immune responses elicited by PLA 5,19 . Instead, this study builds on observed alterations in bioenergetics as well as metabolic reprogramming as drivers of adverse immune responses to polyethylene wear particles 41,42 after total joint replacements and PLA biomaterials 6 . By subcutaneously implanting sterile amorphous PLA, we validated this bioenergetic model by demonstrating metabolic reprogramming, in-vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to respective controls, exposure of primary bone marrow-derived macrophages or mouse embryonic fibroblasts to polyethylene particles decreased bioenergetics in lysed cells (Fig. 1a-b) 22 . Importantly, specific inhibition of complex I by rotenone or metformin did not further decrease ATP levels (Fig.…”
Section: Resultsmentioning
confidence: 89%
“…We have previously uncovered a role for glycolytic reprogramming in the inflammatory response to UHMWPE wear particles. Specific inhibition of different steps in glycolysis prevented the expression of proinflammatory cytokines while stimulating antiinflammatory cytokines 22 . However, in addition to increased glycolysis, elevated mitochondrial oxygen consumption was observed whose role was unclear.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations